Effect of Intercropping Soybean on the Diversity of the Rhizosphere Soil Arbuscular Mycorrhizal Fungi Communities in Wheat Fields. Issue 6 (31st March 2022) - Lu, Xingli
Abstract: The variations of rhizosphere soil arbuscular mycorrhizal fungi (AMF) and their impact mechanism are still unclear under different intercropping systems in the Yellow River Irrigation District of Ningxia, China. A field experiment to study variations in rhizosphere soil AMF diversity and its effects under different planting systems in this area. Three intercropping systems consisting of six rows of spring wheat intercropped with two rows of soybean (RSW), wheat monoculture (RW), and soybean monoculture (RS) were applied. The results showed that the RSW treatment has a 5.6% and 10.0% higher soil organic carbon (SOC) content than the RW and RS plots, respectively. The dominant genera in this study are Glomus and Paraglomus. The Shannon index, Simpson index, Chao1 value, and abundance‐based coverage estimator in the RSW treatment are higher than in the RS plots. Additionally, the multiple linear regression equation suggests that invertase activity is the main impact factor for the Shannon index of AMF. Moreover, the wheat yield in the RSW plot is 11.4% higher than the RW plot. The results suggest that the RSW treatment has great potential for improving soil nutrients, AMF diversity, and wheat yield to sustain soil health and crop production. Abstract : Intercropping grain legumes with non‐legumes has a vital importance on the improvement of biodiversity and crop production. The field experiment reveals that intercropping spring wheat with soybean has great potential for improving soil nutrients, rhizosphere soil arbuscular mycorrhizal fungi diversity, and wheat yield to sustain soil health and crop production.